Cultural transformation: an analysis of the community bylaws and legal mechanisms in combating the practice of 'Kusasa Fumbi' in Malawi - Kumbambe, Tamandani (Department of Public Law, 2025)
This dissertation critically examines the intricate relationship between cultural practices, Malawi's legal framework, and the emergent role of community bylaws in combating the persistent issue of Kusasa Fumbi, a harmful cultural practice affecting the girl child in Malawi. The study addresses fundamental questions regarding the efficacy of community bylaws, the role of domestic and international laws, the prevalence of Kusasa Fumbi in rural regions, and the adverse impacts on girls. The dissertation begins by acknowledging the severity of the issue, noting that sexual initiation rites involving minors infringe upon their human rights, pose health risks, and have enduring adverse effects on their socioeconomic status, access to education and physical and mental well-being. Despite such risks, the practice of Kusasa Fumbi is shielded by cultural beliefs, rarely reported to authorities, and perpetrators often escape prosecution. The limited enforcement of existing laws relating to Kusasa Fumbi is cited as a significant obstacle. The dissertation explores the emergence of community bylaws, primarily led by traditional authorities, as an attempt to address harmful practices in rural Malawi. The study examines these community bylaws and their potential contribute to shielding women and girls from harmful cultural practices. It explores how the community bylaws offer a bridge between formal law and on-the-ground cultural practices. Central to the research is the examination of Malawi's legal framework and its alignment with international and regional standards for protecting girls from harmful rites of passage. The study critically examines the persistence of this harmful cultural practice, deeply entrenched within communities under the guise of tradition and culture. Two key questions are posed: Can community bylaws contribute to combating Kusasa Fumbi? What roles can domestic and international law play in eradicating such oppressive and dehumanising practices? The research aims to highlight the significance of addressing harmful cultural practices, as gender disparities persist due to deeply entrenched cultural attitudes. The study emphasizes the vulnerability of underage girls to such harmful traditions and attitudes, hindering their educational opportunities.